2019
DOI: 10.5006/3110
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion in CO2 Systems with Impurities Creating Strong Acids

Abstract: There are several proposed specifications for CO2 transport regarding how much impurities that can be allowed in the CO2 stream. Many of these specifications are based on health, safety, and environment (HSE) considerations in case of accidental spill, and only limited focus has been on the pipeline integrity. Previous work has demonstrated that many of the impurities that are expected to be present in CO2 captured from flue gasses may react and form corrosive species. The present paper studied impurity reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Comparison of filters from up-and downstream the reduction valve may provide useful information, since the pressure drop over the heated gas regulator may lead to precipitation of certain species (see Figure 6). Previous research [3,10,15] has shown that interaction between impurities may occur when certain types are present, and the concentrations exceed a critical limit. The analysis system is vulnerable to precipitation of solids if they settle inside the analytical instruments.…”
Section: Solidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparison of filters from up-and downstream the reduction valve may provide useful information, since the pressure drop over the heated gas regulator may lead to precipitation of certain species (see Figure 6). Previous research [3,10,15] has shown that interaction between impurities may occur when certain types are present, and the concentrations exceed a critical limit. The analysis system is vulnerable to precipitation of solids if they settle inside the analytical instruments.…”
Section: Solidsmentioning
confidence: 99%
“…Due to the large number of possible impurities, the number of possible chemical reactions is high. The most important reactions that were identified in the Kjeller dense phase CO 2 project (KDC) [3,4,9,15,21] were…”
Section: Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, the captured and compressed CO 2 should not be encumbered with unnecessary and costly cleaning procedures to remove accompanying species, which are called impurities in this paper. Some of these impurities may react and produce strong acids, which could cause severe problems in the transportation and storage systems. It is expected that the captured CO 2 will be transported from the capture site to the storage location as bulk cargo (on ships or trains) or in pipelines.…”
Section: Introductionmentioning
confidence: 99%
“…Crucial in such a tool is the knowledge about reactions, interactions, and solubility of the involved species. Previous work by our research group has identified some of the reactions and interactions that could occur at different concentrations of the expected impurities, and it was shown that sulfuric and nitric acids could form under certain conditions. Hoa et al showed that, at low pressure, the condensation of SO 2 and NO 2 with water resulted in the formation of H 2 SO 4 and HNO 3 , which led to strong pitting and localized corrosion in the presence of H 2 SO 4 , while HNO 3 induced only high general corrosion.…”
Section: Introductionmentioning
confidence: 99%